Quality of the scientific production of UNMSM medicla school researchers - Sogi, Cecilia (2003)
OBJECTIVE: To assess quality of the scientific production of UNMSM Medical School researchers. MATERIAL AND METHODS: San Marcos Research Activities Registry (RAIS) database and full text articles of journals 1991-2000 registered in RAIS. Four hundred and sixty-two articles were categorized and those corresponding to studies were separated. From these a random sample of 20% (n=59) was selected and peer reviewed using Vancouver style as quality standard. Score was assigned to each part of the publication in order to measure inter-rater reliability and to categorize results of the assessment. RESULTS: Inter-rater reliability coefficient varied among sections of the publication; 71,2% of the studies were rated as good-excellent but 80% did not describe statistical procedure and 85% did not communicate ethical issues. CONCLUSION: Vancouver guidelines for the format of articles was useful in order to evaluate their quality.